Macrophage migration inhibitory factor stimulates AMP-activated protein kinase in the ischaemic heart - Miller, Edward J.; Li, Ji; Leng, Lin; McDonald, Courtney; Atsumi, Toshiya; Bucala, Richard; Young, Lawrence H. (Nature, 2008)
The heart under stress AMPK (AMP-activated protein kinase) is a master regulator of many biological processes and is a potential drug target for diseases as diverse as diabetes, cancer, atherosclerosis and ischaemic heart disease. In the ischaemic heart, AMPK protects tissues from injury and apoptosis by promoting glucose uptake. A new study shows that AMPK is activated by the inflammatory cytokine MIF (macrophage migration inhibitory factor), which is released by the heart under ischaemic stress. This throws new light on the nature of the cellular stress response, and highlights low MIF levels as a potential risk marker for patients with coronary artery disease. The protein kinase AMPK protects the ischemic heart from injury and apoptosis by promoting glucose uptake. This paper shows that AMPK is activated by the inflammatory cytokine MIF which is produced and released by the heart under ischemic stress. Understanding cellular response to environmental stress has broad implications for human disease. AMP-activated protein kinase (AMPK) orchestrates the regulation of energy-generating and -consuming pathways, and protects the heart against ischaemic injury and apoptosis 1 . A role for circulating hormones such as adiponectin 2 and leptin 3 in the activation of AMPK has received recent attention. Whether local autocrine and paracrine factors within target organs such as the heart modulate AMPK is unknown. Here we show that macrophage migration inhibitory factor (MIF), an upstream regulator of inflammation 4 , is released in the ischaemic heart, where it stimulates AMPK activation through CD74, promotes glucose uptake and protects the heart during ischaemia-reperfusion injury. Germline deletion of the Mif gene impairs ischaemic AMPK signalling in the mouse heart. Human fibroblasts with a low-activity MIF promoter polymorphism 5 have diminished MIF release and AMPK activation during hypoxia. Thus, MIF modulates the activation of the cardioprotective AMPK pathway during ischaemia, functionally linking inflammation and metabolism in the heart. We anticipate that genetic variation in MIF expression may impact on the response of the human heart to ischaemia by the AMPK pathway, and that diagnostic MIF genotyping might predict risk in patients with coronary artery disease.